Emerging Technologies and Pedagogies in the Curriculum - Yu, Shengquan; Ally, Mohamed; Tsinakos, Avgoustos; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book explores the technologies that can be used in curricula to make education (3z(Bsmarter(3y (Band more adaptive in order to better meet the needs of today$1 (Bs learners. The main emphasis is based on the theory and best practices of incorporating emerging technologies into curricula so as to educate learners in the 21st century. The book provides valuable insights into the future of education and examines which pedagogies are most suitable for integrating emerging technologies. It will help educators and stakeholders design and implement curricula that effectively prepare learners for the challenges of tomorrow.s
Framework/Modes for Emerging Technologies in the Curriculum -- Learning Theories for Using Emerging Technologies in the Curriculum -- Types of Emerging Technologies -- Smart Technologies -- Learning Cell -- Adaptive Learning -- Future (the Next Revolution) of MOOCs -- Double Spiral Learning Model -- Adaptive Open Course -- Interactive Learning Materials -- Connective Learning in the Curriculum -- Problem Based Learning -- Rain Classroom (Interactive Classroom) -- Robotics in the Curriculum -- Fourth Industrial Revolution (4IR) and Its Impact on the Curriculum -- Learning Design Tools for Teachers Using Emerging Technologies -- Mobile and Ubiquitous Learning -- Artificial Intelligence in the Curriculum -- Artificial Intelligence for Language Learning -- Emerging Technologies to Teach Language and Translation -- Internet of Things -- Role of Big data in Learning -- Learning Analytics -- Future Literacy (Knowledge, Skills, and Abilities) -- Others.
Keywords: Educational technology; Education$1 (BData processing.s; Educational Technology; Technology and Digital Education; Computers and Education